Paracoccidioides brasiliensis PbP27 gene : knockdown procedures and functional characterization (2014)
ABSTRACT : Paracoccidioides brasiliensis PbP27 gene encodes a protein localized in both the fungal cytoplasm and cell wall. The parasitic infectious form produces this protein preferentially with the gene’s expression varying between the fungus phylogenetic species. The biological function of the native p27 has yet to be determined during either growth of the yeast or host infection. Therefore, in this study, through the use of antisense RNA technology and Agrobacterium tumefaciens-mediated transformation, we generated mitotically stable PbP27 mutants (PbP27 aRNA) with the goal to evaluate the role of p27 in the biology and virulence of this fungus. PbP27 expression was reduced 60–75% in mutants, as determined by real-time PCR in correlation with a decrease in p27 expression. No alterations in the growth curve or in the ability to shift from mycelia to yeast or from yeast to mycelia were observed in PbP27 aRNA strains; however, we did observe a reduction in cell vitality. Moreover, a decrease in cell viability of PbP27 aRNA yeast cells after interaction with IFNc-stimulated macrophages was detected. Based on these results, we propose that p27 plays a role in yeast cell architecture and represents one of the mechanisms employed by this fungus for its interaction with the monocyte/macrophage system.